Investigation of 2014 flood impacts on river planform and geometry changes in Pahang River, Malaysia - Nur Hishaam bin Sulaiman
Flood is one of the natural disasters that frequently OCCUlT d particularly in Peninsular Malaysia. In December 2014, a major flood hit the East Coast of Peninsular Malaysia which resulted in a variety of implications for the environment, particularly effects of flood to river planform and geometry. The objectives of this research are to investigate the effect of 2014 major flood on river planform and geometryin the mainstream of Pahang River. The study is divided into three stages, namely the upstream, middle stream and downstream of the Pahang River.Type of Lateral Change (TYLAT), Mode of Meander Movement (MOME), and Sinuosity Index method are used to classify and evaluate the river planform changes based on the satellite images from 2010 (before flood) and 2015 (after flood). Bathymetric analysis with the support of Surfer and Geographic Information System ArcGIS software were conducted to display the changes of river's geometry shapes due to 2014 flood. The results obtained reflect change f Meander Progression and changes in Increasing Amplitude indicate high numbers of cases. Respectively, 36 cases and 24 cases were concentrated in the upstream of Pahang River. Braiding changes focused on the downstream of Pahang Riverat Pekan recorded five cases. MOME changes ofExtension and Translationevidently occurred at a high level at upstream, which recorded 23 cases and 14' ca es respectively. Sinuosity Indexof Pahang River shows high percentage of changes occurs in the up tream at Tembeling River and Jelai River with the highest percentage recorded at 45 percent. Sinuosity Index recorded at middle stream shows a significant change with the percentage of 20.7 percent. While at downstream, the inuosity Index recorded three significant changes from 16.0 to 20.3 percent. Based on statistical analysis, significant changes with moderate correlation in R squared value atR2 = 0.6669 was obtained between Sinuosity Index changes and water level that occurred from 2010 to 2015.Meanwhile, using Kriging Interpolation method, local rainfall distribution in the Pahang River Basin shows a high amount of fall occurrence. The concentration area of rainfall recorded was on the highlands, which are located at the North West of Pahang River Basin. Cumulative rainfall increased from 1300mm to 1670mm in December 2014. In January 2015, cumulative rainfall in the Pahang River Basin decreased to 200 mm to 161 mm. In future, for mitigation measure, alternative management is proposed for Pahang River Maintenance such as service of natural flood ponds and flood mitigation projects. Generally, this study is very important to gather information on the effect of 2014 major flood in Pahang River in order to manage the Basin of Tropical River.